Corrosion effects on the seismic response of existing rc frames designed according to different building codes. (1st August 2020) - Berto, Luisa; Caprili, Silvia; Saetta, Anna; Salvatore, Walter; Talledo, Diego
Highlights: RC frames structural assessment in aggressive environmental conditions is performed. Two case studies representative of the Italian building heritage are selected. Corrosion effect on buildings designed with actual and old seismic code is assessed. Corrosion has detrimental effect in RC buildings designed according to old codes. Abstract: Durability problems significantly affect the structural performance of reinforced concrete (RC) buildings: when exposed to aggressive environmental conditions, both steel reinforcing bars and concrete undergo relevant alterations of their mechanical performance (strength and deformation) leading to a general decrease of the bearing capacity of structural elements and, more in general, of the whole construction. Material deterioration can be responsible for the shift of the collapse mode from ductile/flexural mechanisms to brittle/shear ones in relation to the entity of corrosion attack, the materials used (both concrete strength class and reinforcement grade) and the structural details assumed according to the design. As well known, the Italian building stock is made up of structures realized, for the majority, without following specific seismic design features and to resist – mainly – gravitational vertical load combinations, until the introduction of the actual code after the dramatic earthquake event of L'Aquila 2008. For this reason, the deep knowledge of the structural performance of RC buildings realized neglecting (or simplifying) seismic action in presence of corrosion attack becomes a topic of relevant importance to determine possible solutions and improvement at section, element and whole building level. In the present paper, the effects of corrosion on two case study buildings designed following actual and past Italian codes for constructions (i.e. with and without respecting the capacity design approach) are then presented. The structural assessment in aggressive environmental conditions is performed adopting different entity and distribution scenarios of corrosion, taking into consideration the decrease of strength and deformation capacity of constitutive materials and the resulting loss of confinement affecting RC sections, allowing to determine the attainment of the ductile and brittle mechanisms and the modification of the structural performance.